Reduced-Dimension MUSIC for Angle and Array Gain-Phase Error Estimation in Bistatic MIMO Radar - Li, Jianfeng; Zhang, Xiaofei; Cao, Renzheng; Zhou, Ming (IEEE communications letters, 2013)
In this letter, the problem of joint angle and array gain-phase error estimation for bistatic multiple-input multiple- output (MIMO) radar is investigated, and an algorithm for joint estimation with the characteristics of multiple signal classification (MUSIC) is proposed. Through reduced-dimension transform, the angles can be obtained via two one-dimensional peak searches, and the array gain-phase error can be estimated by utilizing the estimated angles. The proposed algorithm can achieve automatically paired estimations of the angles, and is suitable for non-uniform linear array. For the case of separately-located ca-librated sensors, the algorithm can also work well. Furthermore, it has better angle and array gain-phase error estimation performance than the ESPRIT-like algorithm. The simulation results verify the algorithmic effectiveness and robustness of our proposed algorithm.